COVID-19 pandemic: from respect for science to investments in National Health Services - Wilson Jorge Correia Pinto de Abreu (Rev Rene)
January 2020. The world has woken up to a worrying reality. The city of Wuhan, capital of the province of Hubei, China, was struggling with a new virus with enormous transmission capacity. COVID-19 is a severe respiratory disease caused by the Severe Acute Respiratory Syndrome virus (SARS-CoV-2), first identified in December 2019 in Wuhan